Análisis y evaluación para la implementación de inventario en la microempresa CREDIART S.A. - Pin Arteaga, Henry Alexander (2024)
This research project was carried out in the micro-enterprise CREDIART S.A. in the city of Guayaquil, whose general objective is to implement inventory control to evaluate the administration of the entry and exit of merchandise and increase the profitability of the CREDIART microenterprise, dedicated to the marketing of clothing. For this, theoretical bases were established that support the degree project, the techniques used were observation, survey and interview carried out in each department and General Manager.